Antimicrobial Resistance Glides in the Sky—Free-Living Birds as a Reservoir of Resistant Escherichia coli With Zoonotic Potential - Skarżyńska, Magdalena; Zaja̧c, Magdalena; Bomba, Arkadiusz; Bocian, Łukasz; Kozdruń, Wojciech; Polak, Marcin; Wia̧cek, Jarosław; Wasyl, Dariusz (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is one of the most important global health concerns; therefore, the identification of AMR reservoirs and vectors is essential. Attention should be paid to the recognition of potential hazards associated with wildlife as this field still seems to be incompletely explored. In this context, the role of free-living birds as AMR carriers is noteworthy. Therefore, we applied methods used in AMR monitoring, supplemented by colistin resistance screening, to investigate the AMR status of Escherichia coli from free-living birds coming from natural habitats and rescue centers. Whole-genome sequencing (WGS) of strains enabled to determine resistance mechanisms and investigate their epidemiological relationships and virulence potential. As far as we know, this study is one of the few that applied WGS of that number (n = 71) of strains coming from a wild avian reservoir. The primary concerns arising from our study relate to resistance and its determinants toward antimicrobial classes of the highest priority for the treatment of critical infections in people, e.g., cephalosporins, quinolones, polymyxins, and aminoglycosides, as well as fosfomycin. Among the numerous determinants, blaCTX–M–15, blaCMY–2, blaSHV–12, blaTEM–1B, qnrS1, qnrB19, mcr-1, fosA7, aac(3)-IIa, ant(3”)-Ia, and aph(6)-Id and chromosomal gyrA, parC, and parE mutations were identified. Fifty-two sequence types (STs) noted among 71 E. coli included the global lineages ST131, ST10, and ST224 as well as the three novel STs 11104, 11105, and 11194. Numerous virulence factors were noted with the prevailing terC, gad, ompT, iss, traT, lpfA, and sitA. Single E. coli was Shiga toxin-producing. Our study shows that the clonal spread of E. coli lineages of public and animal health relevance is a serious avian-associated hazard.